Long noncoding RNAs-a new dimension in the molecular architecture of the bile acid/FXR pathway. (5th April 2021) - Ma, Yonghe; Harris, Jamie; Li, Ping; Cao, Haiming
Abstract: Bile acids, regarded as the body's detergent for digesting lipids, also function as critical signaling molecules that regulate cholesterol and triglyceride levels in the body. Bile acids are the natural ligands of the nuclear receptor, FXR, which controls an intricate network of cellular pathways to maintain metabolic homeostasis. In recent years, growing evidence supports that many cellular actions of the bile acid/FXR pathway are mediated by long non-coding RNAs (lncRNAs), and lncRNAs are in turn powerful regulators of bile acid levels and FXR activities. In this review, we highlight the substantial progress made in the understanding of the functional and mechanistic role of lncRNAs in bile acid metabolism and how lncRNAs connect bile acid activity to additional metabolic processes. We also discuss the potential of lncRNA studies in elucidating novel molecular mechanisms of the bile acid/FXR pathway and the promise of lncRNAs as potential diagnostic markers and therapeutic targets for diseases associated with altered bile acid metabolism.